Globalisasi dan Perubahan Budaya: Perspektif Teori Kebudayaan Modern - I Gusti Ngurah Mayun Susandhika (Universitas Mahendradatta Denpasar, 2018)
This paper discusses the relevance of culture theories for understanding glo- balization and cultural change taking place in Indonesia. The issue of globalization and cultural change has recently figured prominently in various discourses in Indonesia, es- pecially in relation to the question of how Indonesia is cultural identities should be main- tained in the face of such a global process. This paper argues that the contemporary cul- ture theory can help us understand such concepts as national culture and identity not as a static, essentialist entity, but rather as a dynamic social construction that is continuously reproduced and innovated by individual subjects. Such an argument is put forth in this paper by introducing aspects of culture theory that have not received much attention in Indonesia, i.e. practice, process, context and discourse concerning cultural construction.